The Position of Auxiliary Organ in Government System of West Java Provincial Government - Abdillah Abdillah; Nandang Alamsah Deliarnoor; Neneng Yani Yuningsih; Fatmawati Fatmawati (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2020)
This Article aims to explain how the West Java Quick Response position in the West Java regional government system 2018-2020 as an auxiliary institution outside the main government institutions is a new problem in the West Java regional government system. This type of research is qualitative with descriptive type. Data collection techniques are observation, interview, and documentation. The number of informants are 11 people who are determined proportionally. The results showed that the position of West Java Quick Response in the local government system in West Java 2018-2020 by looking at the two principles of independent institution criteria, namely First, the Policy Principle, and second, the Tenure or not-Political Party Principle. It can be concluded that West Java's Quick Response position in the regional government system of West Java 2018-2020 is not only a supporting institution, which helps, and supports humanitarian and social tasks, as well as the political stability of the governor of West Java as the regional head. West Java Quick Response in addition to being an innovation in West Java regional government in an effort to realize Good Governance. Although the position JQR cause problem, but it is also an effective step in the politics of the governor of West Java in carrying out leadership as the regional head in the government of West Java.